MEC (mitoxantrone, etoposide, and cytarabine) induces complete remission and is an effective bridge to transplant in acute myeloid leukemia. (7th April 2020) - Marconi, Giovanni; Talami, Annalisa; Abbenante, Maria Chiara; Sartor, Chiara; Parisi, Sarah; Nanni, Jacopo; Bertamini, Luca; Ragaini, Simone; Olivi, Matteo; de Polo, Stefano; Cristiano, Gianluca; Fontana, Maria Chiara; et al.
Abstract: Introduction: Clinical response and chemosensitivity of relapse or refractory AML patients were evaluated after rescue and bridge‐to‐transplant MEC (mitoxantrone, etoposide, and cytarabine) regimen. Methods and Patients: Fifty‐five consecutive AML patients were treated with MEC from 2009 to 2018. Chemosensitivity was evaluated by WT1 quantification. Results: 27/55 patients (49.1%) had AML resistant to induction and 28/55 patients (50.9%) had AML relapse. 25/55 patients (45.5%) achieved a CR after one course of MEC, and 12 patients (21.8%) achieved WT1 negativity. In 12 patients, a second MEC was administered. Four out of 12 patients improved significantly their response with the 2nd MEC. MEC was an effective bridge to transplant, 32/55 patients (58.2%) received an allogenic stem cell transplant. Median overall survival (OS) from MEC was 455 days (95% CI 307‐602 days.); patient with WT1 negative CR had the best OS ( P <.000). Conclusion: WT1 is a useful marker of chemosensitivity after MEC as rescue and bridge‐to‐transplant therapy.